T cell receptor binding affinity governs the functional profile of cancer‐specific CD8+ T cells. (May 2015) - Tan, M. P.; Gerry, A. B.; Brewer, J. E.; Melchiori, L.; Bridgeman, J. S.; Bennett, A. D.; Pumphrey, N. J.; Jakobsen, B. K.; Price, D. A.; Ladell, K.; Sewell, A. K.
Summary Antigen‐specific T cell receptor (TCR) gene transfer via patient‐derived T cells is an attractive approach to cancer therapy, with the potential to circumvent immune regulatory networks. However, high‐affinity tumour‐specific TCR clonotypes are typically deleted from the available repertoire during thymic selection because the vast majority of targeted epitopes are derived from autologous proteins. This process places intrinsic constraints on the efficacy of T cell‐based cancer vaccines and therapeutic strategies that employ naturally generated tumour‐specific TCRs. In this study, we used altered peptide ligands and lentivirus‐mediated transduction of affinity‐enhanced TCRs selected by phage display to study the functional properties of CD8+ T cells specific for three different tumour‐associated peptide antigens across a range of binding parameters. The key findings were: (i) TCR affinity controls T cell antigen sensitivity and polyfunctionality; (ii) supraphysiological affinity thresholds exist, above which T cell function cannot be improved; and (iii) T cells transduced with very high‐affinity TCRs exhibit cross‐reactivity with self‐derived peptides presented by the restricting human leucocyte antigen. Optimal system‐defined affinity windows above the range established for natural tumour‐specific TCRs therefore allow the enhancement of T cell effector function without off‐target effects. These findings have major implications for the rational design of novel TCR‐based biologics underpinned by rigorous preclinical evaluation.